From open weather data to accessible weather information services for smallholder farmers - Msengezi, Chipo; Addison, Chris (Technical Centre for Agricultural and Rural Cooperation, 2018)
Weather data and services derived from weather data have a high potential to enhance support for smallholder farmers in taking operational decisions on farm management. Plant growth is driven by weather variables and therefore agricultural production is directly dependent on weather conditions. Many agricultural activities (e.g. sowing, harvesting, and fertiliser application) are dependent on weather conditions for planning and effectiveness. Given this, all agricultural stakeholders are interested in some form of meteorological data. This Policy Brief outlines the importance and benefits that can be derived from weather data in agriculture and nutrition, the challenges in the weather data value chain and recommendations to address these challenges.